1998
DOI: 10.1007/s002489900102
|View full text |Cite
|
Sign up to set email alerts
|

Post-Sampling Changes in Microbial Community Composition and Activity in a Subsurface Paleosol

Abstract: A B S T R A C TLaboratory storage of deep vadose zone sediments has previously resulted in an increase in the abundance of cultured microorganisms by as much as 10,000-fold, without concomitant increases in total microscopic counts. In the present study, factors contributing to the time-dependent stimulation of various microbiological parameters were examined during a 224 d post-sampling period, using a factorial-design experiment that partitioned the effects of storage time, sediment condition (intact blocks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
1

Year Published

2000
2000
2004
2004

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 38 publications
0
13
1
Order By: Relevance
“…Additional support for this hypothesis was provided by Kiefi et al (1993) who observed bacterial cells, by direct microscopy, in the range of lo6 to lo7 cells/g in pristine Hanford formation sediments. Also, studies by our laboratory Brockman et al 1998) and others 'bd = below detection or less than 2.0 log colony forming units (CFU)/g. bsediments subjected to artificial recharge, contamination by past site activities ).…”
Section: D45 Conclusion Of Sandt Investigations Of Geochemistry and mentioning
confidence: 99%
“…Additional support for this hypothesis was provided by Kiefi et al (1993) who observed bacterial cells, by direct microscopy, in the range of lo6 to lo7 cells/g in pristine Hanford formation sediments. Also, studies by our laboratory Brockman et al 1998) and others 'bd = below detection or less than 2.0 log colony forming units (CFU)/g. bsediments subjected to artificial recharge, contamination by past site activities ).…”
Section: D45 Conclusion Of Sandt Investigations Of Geochemistry and mentioning
confidence: 99%
“…After contamination of pristine soil with petroleum, an increase in microbial activity, but a decrease in diversity, is generally observed (see [8][9][10][11][12][13][14][15]). However, most studies with artificially polluted soils were performed in the laboratory, and significant effects on the activity and composition of the microbial communities in controls without contamination were also observed, as a result of the incubation process [10,22]. Thus, the transferability of long-term laboratory studies to the field situation is often questionable.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the need for rapid initiation of analyses after sediment sample acquisition was demonstrated for measurements of in situ microbial properties [30]. Subsequently, the experience gained was used in studies of the environmental conditions under which microorganisms exist in deep continental hydrocarbon reservoirs.…”
Section: Continental Sedimentary Rocksmentioning
confidence: 99%